Association between metabolic syndrome and chronic obstructive pulmonary disease development in young individuals: a nationwide cohort study - Ock-Hwa Kim; Kyu Na Lee; Kyungdo Han; In Young Cho; Dong Wook Shin; Sei Won Lee (Respiratory Research)
Abstract Background The association between metabolic syndrome (MetS) and chronic obstructive pulmonary disease (COPD) has not been studied well, particularly in young individuals. We investigated the risk of COPD development in young individuals based on MetS and its components. Methods We used the Korean National Health Information Database to identify 6,891,400 individuals aged 20–39 years who participated in the national health check-up service between 2009 and 2012. Then, we identified individuals with MetS and investigated COPD development based on health insurance claims. Cox proportional hazard regression models were used to calculate the adjusted hazard ratio (aHR) for the risk of COPD development. Results During a mean follow-up period of 8.35 years, 13,784 individuals were newly diagnosed with COPD. MetS was associated with an increased risk of COPD (aHR, 1.18; 95% confidence interval [CI], 1.11–1.24). Among the MetS components, except for hyperglycemia, abdominal obesity (aHR, 1.27; 95% CI, 1.19–1.34), hypertension (aHR, 1.05; 95% CI, 1.01–1.10), hypertriglyceridemia (aHR, 1.11; 95% CI, 1.07–1.16), and low high-density lipoprotein cholesterol levels (aHR, 1.16; 95% CI, 1.11–1.22) were significantly associated with COPD development. A higher number of MetS components correlated with an increased risk of COPD development, with the highest risk observed when all five MetS components were present (aHR, 1.55; 95% CI, 1.28–1.87). Conclusion MetS was associated with COPD development in young individuals. The risk of COPD development increased along with the increasing number of MetS components. These findings suggest that careful monitoring for COPD development is necessary in young individuals with MetS, especially those with multiple components of MetS.